Stigma reduction interventions in people living with HIV to improve health-related quality of life. Issue 2 (February 2020) - Andersson, Galit Zeluf; Reinius, Maria; Eriksson, Lars E; Svedhem, Veronica; Esfahani, Farhad Mazi; Deuba, Keshab; Rao, Deepa; Lyatuu, Goodluck Willey; Giovenco, Danielle; Ekström, Anna Mia
Summary: As the UNAIDS 90-90-90 targets for people living with HIV are increasingly being reached in many contexts, health-related quality of life, the so-called fourth 90, warrants special attention. HIV-related stigma and discrimination are major barriers for overall health-related quality of life despite impressive clinical and virological improvements in HIV care. There is a scarcity of well designed intervention studies that document stigma reduction in people living with HIV and few studies that specifically assess the effect of stigma on health-related quality of life. Further, few interventions target discrimination from providers outside of HIV-specific care or involve people living with HIV in both the design and implementation. Lastly, evidence on methods to reduce stigma in several underepresented key populations and geographical regions is insufficient and research on intersectional stigma (ie, the convergence of multiple stigmatised identities) needs further attention.